Optimal solutions for a 33 KV loop supplied by infinite source - Mahmoud, Ethmane Isselem Arbih; Abbou, Ahmed; Mahmoud, Abdel Kader; Ketab, Mohamed Moustapha (Institute of Advanced Engineering and Science, 2025)
This paper presents an analysis and explores the potential an infinite generation system to accommodate the domestic load growth of the 33 KV loop network from 2025 to 2040. The study involves assessing the current state of the network, focusing on voltage levels, loading lines, and transformers, to ensure they operate within the permissible loading limits of the system. It is assumed that the loop is supplied by an infinite source. A numerical model using the Gauss-Seidel method is implemented and executed on the PSS/E simulator. We will simulate the current network state and analyze the voltage profile, which should range between 0.95 and 1.05 pu. Next, we forecast the demand based on the industrial growth of the cities interconnected to this 33 kV loop. Analysis the simulation results will demonstrate the possibility of increasing the transit active power and controlling the reactive power in the system at 2040 year. Indeed, we propose solutions to address the identified critical issues to meet the projected demand. These solutions involve doubling the power capacity of the existing transformers. The proposed system will provide industrial consumers with reduced load imbalances and better control over voltage fluctuations caused by rapid variations in reactive power demand.